Sexuality and gender collected essays - Loader, William R. G. 1944-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2021)
Cover -- Title -- Preface -- Table of Contents -- Introduction -- Sexuality and the Septuagint -- 1. Sexuality and Ptolemy's Greek Bible. Genesis 1-3 in Translation. "... Things which they altered for King Ptolemy" (Genesis Rabbah 8.11) -- 2. The Beginnings of Sexuality in Genesis LXX and Jubilees -- 3. Genesis 3:16-19 LXX in Reception. Observations on its Use in Early Judaism and Christianity to ca 100 CE -- 4. Attitudes towards Sexuality in the LXX Translations of Contentious Texts -- 5. Proverbs' "Strange Woman": Image and Reality in Proverbs and Ben Sira, Hebrew and Greek -- 6. The "Strange Woman" in Proverbs, LXX Proverbs, and Aseneth -- Sexuality and the Pseudepigrapha -- 7. Jubilees and Sexuality -- 8. Jubilees and Sexual Transgression: Reflections on Enochic and Mosaic Tradition -- 9. Sexuality in The Testaments of the Twelve Patriarchs and the New Testament -- 10. Sexuality and Eschatology: In Search of a Celibate Utopia in Pseudepigraphic Literature -- 11. "Not as the Gentiles": Sexual Issues at the Interface between Judaism and its Greco-Roman World -- Sexuality and the Dead Sea Scrolls -- 12. Attitudes towards Sexuality in Qumran and Related Literature - and the New Testament -- 13. Eschatology and Sexuality in the So-Called Sectarian Documents from Qumran -- 14. Sexuality Issues and Conflict Development in Qumran Literature -- Sexuality and Gender in the Emerging Christian Movement -- 15. Sexuality and the Historical Jesus -- 16. Genesis 2:24 and the Jesus Tradition -- 17. Did Adultery Mandate Divorce? A Reassessment of Jesus' Divorce Logia -- 18. Sexuality in the World of Jesus and the Future -- 19. Does Matthew's Handling of Sexuality Issues Shed Light on Its Context? -- 20. The Intermarriage Issue in Early Jewish Theologies and the New Testament.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung